MANUSIA DAN SAINS DALAM PERSPEKTIF AL-QUR’AN - Azhar Azhar (Lantanida Journal, 2016)
Islam requires its adherents to study and develop science. Human knowledge continues to evolve with the times and the discovery of the secrets of nature. The Qur'an applies to all ages, even many things that can not be understood by man today, as many things also have begun to be understood over the course of time. All human beings have an interest in knowing the basics of natural science, because starting from the oxygen gas to breathe, the food and the necessary medicines, the environment and the natural disasters all are related to the natural sciences. Without the power of science how can humans can understand the universe to see the greatness of Allah swt. Therefore, the increase of human resources in Islamic society becomes a necessity.